Identyfikacja płci osobnika odkrytego na cmentarzysku z X/XI wieku w Sowinkach koło Poznania na podstawie badań genetycznych szczątków włosów - Krzyszowski, Andrzej; Stochaj, Marian; Pawłowski, Ryszard; Welz, Anna (Polskie Towarzystwo Antropologiczne, 1996)
Identification of sex of the skeleton recovered from the cemetery at Sowinki near Poznań on the basis of genetic analysis of hair remains.
Identification of sex of the skeleton recovered from the cemetery at Sowinki near Poznań on the basis of genetic analysis of hair remains